Comparable survival in ischemic and nonischemic cardiomyopathy secondary to ventricular tachyarrhythmias and aborted cardiac arrest - Rusnak, Jonas; Behnes, Michael; Schupp, Tobias; Weiß, Christel; Lang, Siegfried; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Ansari, Uzair; et al. (Coronary artery disease, 2019)
ObjectivesThe study sought to assess the impact of ischemic cardiomyopathy (ICMP) and nonischemic cardiomyopathy (NICMP) on secondary survival in patients presenting with ventricular tachyarrhythmias and aborted sudden cardiac arrest (SCA).BackgroundData regarding the outcome of patients with ICMP o
Gesehen am 18.07.2019